Assessing microstructure changes in potassium dihydrogen phosphate crystals induced by mechanical stresses. (1st March 2016) - Hou, Ning; Zhang, Yong; Zhang, Liangchi; Zhang, Feihu
Abstract: This paper proposes a new way of damage characterization with the aid of the grazing incidence X-ray diffraction technique. The results showed that a machined potassium dihydrogen phosphate (KDP) crystal contains a lattice misalignment structure in its shallow subsurface layer. Dislocation motions are the primary mechanism of the structural evolution from the KDP's monocrystalline to the misaligned crystalline structure. These findings allow to identify the underlying causes of lower laser damage threshold (LDT) of KDP components produced by ultra-precision machining. Graphical abstract: